Analysis of Problems of Science Teachers in Learning of Prakarya for the Mentoring Activities of Applied Science in Sijunjung Regency - renol afrizon; H Hidayati; Relsas Yogica (Pelita Eksakta, 2019)
Natural science teachers at Sijunjung Regency Junior High School must teach science and crafts subjects in meeting the teaching load in their respective schools. 65% of the science teachers at the Sijunjung district junior secondary school teach prakarya subjects. Provision of assistance activities can be used as a solution that is expected to motivate teachers to continue to improve their competence. Before the service community activities are carried out then disseminate questionare to see the initial conditions in more detail in the learning of prakarya so that it can be used as a reference in the implementation of applied science mentoring activities in prakarya learning. The questionnaire was distributed using the Gutman scale. The distribution of the questionnaire was carried out on July 13, 2019 before the mentoring activities began. Analysis of the data used is descriptive data analysis. The analysis showed that the junior high school science teachers in Sijunjung Regency were still not professional in teaching crafts at school. This is due to the still lack of application of science / science in learning prakarya. Prakarya subjects have four material aspects, namely: crafts, engineering, cultivation, and processing. The material aspect of crafts is more dominantly taught by science teachers in craft subjects even though this material aspect is more appropriate to be taught by arts / culture teachers. In addition, there are still very few natural science teachers who are able to compile craft teaching materials. Therefore, the results of this initial condition analysis can be used as a reference in the implementation of applied natural science mentoring activities in prakarya learning so that it suits the needs.